Design of Elementary School’s Desk and Chair to Overcome Mismatch Between School Furniture and Students - Nindya Laksita Larasati; Irwan Iftadi; Taufiq Rochman (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
Children spend a large time on school furniture in the classroom. Many studies before evaluate the extent of a possible mismatch between school furniture and students. However, the observations in public elementary schools with 159 students in Surakarta, Indonesia, showed that there are school furniture mismatch between the students’ body size and their activity in the classroom. This study was carried out in order to overcome the mismatch and describes the development of a dynamic furniture designed to be appropriate for the sizes of students. The students’ anthropometry data were incorporated in the design process for the school furniture and the designs come in many various combinations to encourage production of ergonomically suitable classroom furniture.